Cigarette Smoking, a Risk Factor for Chronic Subclinical Inflammation and a Predictor of Metabolic Syndrome in Adult Healthy Population of Bangladesh - Rehnuma, Behterin; Eva, Sohely Najneen; Ibrahim, Mohammad; Nasir, Tareak Al; Ali, Liaquat (Pulse, 2016)
Background and Aims: Smoking is a classical and major risk factor for cardiovascular disease. Inflammatory activators and metabolic disorders are the mediators of smoking-induced atherosclerotic progression. The aim of the present study was to investigate whether smoking alter inflammatory or metabolic status and affect subclinical atherosclerosis in apparently healthy persons. Methods: A total number of 149 adults, age 30-60 yrs, were recruited in the study. Participants were divided into sub-groups of smokers (76) and non-smokers (73). All participants were interviewed and underwent physical examinations and blood collection. High-sensitivity C reactive protein (Hs-CRP) was measured to assess degree of underlying inflammation. Fasting plasma glucose and lipid profile were measured to assess metabolic condition. Data were analyzed using statistical Package for Social Program (SPSS) for Windows version 17. Results: Hs-CRP (p=0.017), Fasting glucose (p=0.003), Triglyceride (p=0.005) was significantly high in smokers in comparison with nonsmokers. BMI (p=0.012) and BFM (%) (p= <0.001) showed significantly lower in comparison with the counterpart. HDL-c (p=.030) was also significantly lower in smoker group than non-smoker group. In Spearmans correlation analyses Triglyceride (p=0.037) and smoking (p= 0.042) showed positive correlation with Hs-CRP. HDL-c is less in smoker subjects but not statistically up to the significant level. Conclusion: The rising Hs-CRP concentration reflects presence of chronic subclinical inflammation in middle aged Bangladeshi smokers and thus may have a risk for future cardiovascular disease. Pulse Vol.8 January-December 2015 p.30-37